Highly pathogenic natural monoclonal antibody B4-IgM recognizes a post-translational modification comprised of acetylated N-terminal methionine followed by aspartic or glutamic acid. (May 2023) - Kulik, Liudmila; Renner, Brandon; Laskowski, Jennifer; Thurman, Joshua M.; Michael Holers, V.
Abstract: The natural monoclonal antibody B4-IgM recognizes murine annexin 4 (mAn4) and exacerbates ischemia-reperfusion injury in many mouse models. During apoptosis, the intracellular mAn4 protein translocates to the membrane surface, remaining attached to the outer membrane leaflet where it is recognized by the anti-mAn4 B4-IgM antibody. B4-IgM does not recognize human annexin 4 (hAn4). However, the B4-IgM antibody epitope was detected by Western blot of unknown human proteins and by flow cytometry on all studied human cell lines undergoing apoptosis and on a minor subset of healthy cells. The B4-IgM antibody also recognizes the epitope on necrotic cells in cytoplasmic proteins, apparently entering through pores large enough to allow natural antibodies to penetrate the cells and bind to the epitope expressed on self-proteins. Using proteomics and site-directed mutagenesis, we found that B4-IgM binds to an epitope with post-translationally modified acetylated N-terminal methionine, followed by either glutamic or aspartic acid. The epitope is not induced by apoptosis or injury because this modification can also occur during protein translation. This finding reveals an additional novel mechanism whereby injured cells are detected by natural antibodies that initiate pathogenic complement activation through the recognition of epitopes that are shared across multiple proteins found in variable cell lines. Highlights: B4-IgM epitope is a protein post-transcriptional modification. B4-IgM is universal apoptosis and injury independent epitope. N-terminal Met acetylation and Glu(2) or Asp(2) as an epitope for nAb B4-IgM. N-terminal Met acetylation is a common species-independent protein modification. Natural B4-IgM penetrates necrotic cells and binds epitope on cytoplasmic self-proteins.